Optimization of electronically monitored non-adherence in highly adherent renal transplant recipients by reducing the dosing frequency – a prospective single-center observational study - Lieb, Marietta; Schiffer, Mario; Erim, Yesim (Patient Preference and Adherence, 2020)
Background: Non-adherence (NA) after renal transplantation poses a major risk for allo-graft rejection, graft loss, and patient mortality. Yet, there is still ambiguity about its etiology and its possible relationships with patient-related factors. In order to prevent poor outcomes after transplantation, it is crucial to gain a more refined understanding of potential determi-nants, to identify patients at risk, and to intervene accordingly. The objective of this study was to assess potential risk factors of NA by prospectively applying electronic monitoring. Materials and Methods: This was a single-center prospective observational study. Prior to study initiation, sociodemographic, biomedical, and psychosocial variables (depression, health-related quality of life, self-efficacy, social support, attachment, experiences and attitudes towards immunosuppressive medication, emotional responses after organ transplantation, satisfaction with information about immunosuppressive medication, and perceptions and beliefs about medications) were assessed. Thereafter, immunosuppressive adherence behavior was measured prospectively via electronic monitoring (EM, VAICA©) during a 3-month period to receive the percentage frequency of Taking and Timing Adherence (±2h, ±30min) for each patient. Focus of this study was the phase of medication implementation. Results: A total of 78 patients participated in our study (mean age 55.28, 56% male). We found rates of 99.39% for Taking Adherence, 98.34% for Timing Adherence ±2h, and 93.34% for Timing Adherence ±30min, respectively. Multiple regression analyses revealed that the type of medication could significantly predict Taking Adherence. Patients receiving Advagraf© (once daily) depicted better Taking Adherence than patients receiving Prograf© (twice daily) (p=0.04). No associations were found for Timing Adherence (±2h, ±30min). Sociodemographic, biomedical, or psychosocial variables were not found to be associated with adherence behavior. Discussion: In highly adherent populations, only a few factors can be altered to improve adherence. Changing the immunosuppressive regimen from twice-daily to once-daily could be an option for optimizing adherence. However, risk factors for NA could be different in a less adherent population.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Adherence; Electronic monitoring; Immunosuppressive medication; Patient-related factors; Psychosocial variables